Allergen and Epitope Targets of Mouse-Specific T Cell Responses in Allergy and Asthma - Schulten, Véronique; Westernberg, Luise; Birrueta, Giovanni; Sidney, John; Paul, Sinu; Busse, Paula; Peters, Bjoern; Sette, Alessandro (Frontiers in Immunology, 2018)
Mouse allergy has become increasingly common, mainly affecting laboratory workers and inner-city households. To date, only one major allergen, namely Mus m 1, has been described. We sought to identify T cell targets in mouse allergic patients. PBMC from allergic donors were expanded with either urine or epithelial extract and subsequently screened for cytokine production (IL-5 and IFNγ) in response to overlapping peptides spanning the entire Mus m 1 sequence, peptides from various Mus m 1 isoforms (major urinary proteins (MUPs), peptides from mouse orthologs of known allergens from other mammalian species and peptides from proteins identified by immunoproteomic analysis of IgE/IgG immunoblots of mouse urine and epithelial extracts. This approach let to the identification of 106 non-redundant T cell epitopes derived from 35 antigens. Seven T cell-activating regions were defined in Mus m 1 alone. Moreover, our data show that immunodominant epitopes were largely shared between Mus m 1 and other MUPs even from different species, suggesting that sequence conservation in different allergens is a determinant for immunodominance. We further identified several novel mouse T cell antigens based on their homology to known mammalian allergens. Analysis of cohort-specific T cell responses revealed that rhinitis and asthmatic patients recognized different epitope repertoires. Epitopes defined herein can be formulated into an epitope “megapool” used to detect mouse-specific T cell responses directly ex vivo. This unbiased analysis of T cell epitopes provides a good basis for future studies to increase our understanding of the immunopathology associated with MO-allergy and asthma.